Prespektif Pembelajaran Matematika Menggunakan Sistem Daring di MI PUI Kemped Wirakanan Selama Pandemi Covid-19 - Rizky Yuniar; Aan Juhana Senjaya; Farid Gunadi (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2021)
This study aims to see the process of implementing mathematics learning through an online system, as well as the perspectives of teachers, parents, and students on the implementation of online learning during the Covid-19 virus pandemic. This research uses phenomenological qualitative research. Data collection using interview techniques and literature study. The subjects in this study were teachers, parents, and grade VI students of MI PUI Kemped Wirakanan in the 2020/2021 school year. Based on the results of the study, it was found that several obstacles caused the online learning process to be less effective due to lack of reference material, students did not understand the material provided by the teacher, not all students had cellphones, spending increased to buy quotas. From a perspective, researchers did not find respondents who agreed with online learning that was carried out in remote villages at the primary school level.